The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/ju.0000000000001071
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Management and Outcomes among Patients with Urothelial Carcinoma Undergoing Radical Cystectomy from 1995 to 2015: The Memorial Sloan Kettering Experience

Abstract: To evaluate trends in oncologic characteristics and outcomes, as well as perioperative management, among patients undergoing radical cystectomy at Memorial Sloan Kettering from 1995 to 2015. Materials and Methods:We retrospectively reviewed our institutional database to analyze changes in disease recurrence probability, cancer-specific and all-cause mortality, incidence of muscle-invasive bladder cancer, use of perioperative chemotherapy, rate of positive soft-tissue surgical margins, and lymph node yield. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Six articles analyzed the 5-year DMR in RCTs and tested the overall heterogeneity (Chi 2 =1.68, df =5, I 2 =0%, and P=0.89>0.1). The analysis results of the FEM indicated that the 2 groups showed no statistically observable difference, which was consistent with the findings of Almassi et al (2020) (19).…”
Section: Discussionsupporting
confidence: 91%
“…Six articles analyzed the 5-year DMR in RCTs and tested the overall heterogeneity (Chi 2 =1.68, df =5, I 2 =0%, and P=0.89>0.1). The analysis results of the FEM indicated that the 2 groups showed no statistically observable difference, which was consistent with the findings of Almassi et al (2020) (19).…”
Section: Discussionsupporting
confidence: 91%
“…In general, younger patients tend to be healthier, with favorable immune function and nutritional status as well as a lower risk of comorbidities and fewer treatment-related complications. Previous studies have suggested that younger patients prefer to undergo more complete, radical, and combined treatment modalities than older patients (e.g., LND or extensive LND during RC combined with chemotherapy)-a finding also reflected in our study (13)(14)(15)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Indeed, in our study, rates of chemotherapy and the median number of LNE were higher in patients <50 years of age than in patients ≥80 years of age.…”
Section: Subgroup Analysissupporting
confidence: 79%
“…LN+, lymph node positivity; NMIBC, non-muscle-invasive bladder cancer.with the LNE while ignoring the impact of age on LN+. In their analysis of data from patients with UC undergoing RC, Almassi et al observed that LNE increased (7 to 24), while LN+ decreased (19% to 8.7%), from 1995 to 2015(20). However, they did not group patients by age for further discussion.…”
mentioning
confidence: 99%
“…Thanks to the improvement of surgical methods and medical therapy, great progress has been made in the treatment of bladder cancer. However, the relapse and metastasis after operation has not been solved, and the 10-year survival rate is still unsatisfied [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%